PENGGUNAAN KOMUNIKASI INSTRUKSIONAL OLEH PENDIDIK DI TAMAN PENDIDIKAN AL QUR’AN - April, Ismaliza (JIV-Jurnal Ilmiah Visi, 2009)
The general purpose of this research was to explore the utilization of instructional communication by the teachers in the Al Qur’an Education Institution. Specifically the research aimed at describing the use of instructional communication by the teachers based on verbal communication, non-verbal communication, and communication with media. The resultf of the research shows that the teachers of the Al Qur’an Education Institution of Husnul Khatimah has been using instructional communication properly. Eventhough, this research gives some suggestions to improve the teachers` competence in using the instructional communication.